2013
DOI: 10.1164/rccm.201211-2104oc
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Bronchoscopic Navigation Combined with Ultrathin Bronchoscopy. A Randomized Clinical Trial

Abstract: VBN-assisted ultrathin bronchoscopy does not improve the diagnostic yield for peripheral pulmonary lesions. However, the method improves the diagnostic yield for lesions in the subcategories (right upper lobe, invisible, peripheral third), warranting further study. Clinical trial registered with www.umin.ac.jp/ctr/ (UMIN 000001536).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(162 citation statements)
references
References 37 publications
5
154
1
2
Order By: Relevance
“…In a randomized control trial, Oki and colleagues found that the diagnostic yield of transbronchial biopsies performed using multimodal devices (EBUS, fluoroscopy, and virtual bronchoscopic navigation guidance) was higher using the ultrathin bronchoscopy method (74%) compared to the combination of thin bronchoscopy with a guide sheath (59%) (43). While the addition of virtual bronchoscopic navigation alone to ultrathin bronchoscopy did not improve the overall diagnostic yield for peripheral pulmonary lesions, the subgroup of patients with lesions in the right upper lobe or peripheral third of the lung demonstrated higher yield with such a combination (44).…”
Section: Thin and Ultrathin Bronchoscopymentioning
confidence: 96%
“…In a randomized control trial, Oki and colleagues found that the diagnostic yield of transbronchial biopsies performed using multimodal devices (EBUS, fluoroscopy, and virtual bronchoscopic navigation guidance) was higher using the ultrathin bronchoscopy method (74%) compared to the combination of thin bronchoscopy with a guide sheath (59%) (43). While the addition of virtual bronchoscopic navigation alone to ultrathin bronchoscopy did not improve the overall diagnostic yield for peripheral pulmonary lesions, the subgroup of patients with lesions in the right upper lobe or peripheral third of the lung demonstrated higher yield with such a combination (44).…”
Section: Thin and Ultrathin Bronchoscopymentioning
confidence: 96%
“…One study showed that in combination with ultrathin bronchoscopy, VBN did not improve the diagnostic yield for peripheral pulmonary lesions. 17) In our study, 5 cases were assisted by VBN but this factor may not affect the results. Thus, delicate route selection with VBN may not be necessary for PPLs that do not have a bronchus sign because GS-TBNA can reach the PPL directly by piercing through the bronchial wall.…”
Section: Discussionmentioning
confidence: 60%
“…For machinegenerated virtual bronchoscopic navigation (VBN), several systems are now available. Studies have shown the efficacy of VBN for lesions (4,(14)(15)(16). Electromagnetic navigation bronchoscopy is another modality for image guidance (17,18).…”
Section: Aspects Of Biopsymentioning
confidence: 99%